Examining the Existing Criteria for the Evaluation of Window Ejected Plume Attachment - Jianlong Xing; Chaoting Nie; Bin Zheng; Lei Miao (Fire)
Both single-skin and double-skin glass facades are extensively employed in commercial high-rise buildings and are gaining increasing popularity. However, the capability to deploy firefighting agents in such ultra-high structures remains limited and has been minimally investigated. To provide guidance for single-layer exterior wall fire protection, this study examines the impact of vertical walls on window ejected plumes by simulating the upper portion of jet plumes using a square burner flame. Experimental and numerical simulations were conducted. The findings revealed that plumes from propane burners could attach to the wall even when LE. burner fire > 0.7W, contradicting previous criteria. This discrepancy arises because prior studies underestimated the induced pressure difference in large fires. This pressure difference propels the plume toward the wall, behaving like a rigid body.